A Comparison of Operative Time and Intraoperative Blood Volume Loss Between Stemless and Short‐stem Anatomic Total Shoulder Arthroplasty: A Single Institution's Experience. (20th July 2022) - Gruson, Konrad I.; Lo, Yungtai; Stallone, Savino; Qawasmi, Feras; Lee, Sung; Shah, Priyam
Abstract : Introduction: There has been increasing interest in the use of stemless humeral implants for total shoulder arthroplasty when compared with both short-stem (SS) and standard-length implants. Although evidence for decreased surgical time and blood loss exists for stemless versus standard-length stems, far less literature exists comparing these clinical parameters for stemless versus SS implants. Methods: A retrospective review of consecutive anatomic total shoulder arthroplasty (aTSA) cases conducted by a single, fellowship-trained shoulder surgeon was undertaken from January 2016 through January 2022 with the exception of March 2020 through January 2021 secondary to the COVID-19 pandemic. Demographic patient and surgical data, including age, sex, body mass index, American Society of Anesthesiologists score, age-adjusted Charlson Comorbidity Index, prior ipsilateral shoulder arthroscopy, surgical time, use of a Hemovac drain and/or tranexamic acid, hospital length of stay (LOS), and both postoperative day #1 (POD 1) and discharge visual analog scores. The use of a stemless or SS implant was recorded. Intraoperative total blood volume loss (TBVL) was calculated, in addition to the need for either intraoperative or postoperative transfusions. Nonparametric analysis of covariance was used to examine effects of stemless versus SS aTSA on surgical time and intraoperative TBVL adjusted for demographic, clinical, and surgical variables. Results: There were 47 SS and 83 stemless anatomic implants included, of which 74 patients (57%) overall were women. The median surgical time for the stemless cohort was 111 minutes (IQR 96-130) versus 137 minutes (IQR 113-169) for the SS cohort ( P < 0.00001). The median intraoperative TBVL for the stemless cohort was 298.3 mL (IQR 212.6-402.8) versus 359.7 mL (IQR 253.9-415.0) for the SS cohort ( P = 0.05). After multivariable regression analysis, use of stemless humeral implants was independently associated with both decreased surgical time and intraoperative blood loss ( P < 0.001 and P = 0.005, respectively). There was a shorter median hospital LOS in the stemless group (2 days [IQR 1-2] versus 2 days [IQR 2-3], P = 0.03). The visual analog score pain score at discharge was lower among the stemless cohort (0 [IQR 0-3] versus 4 [IQR 2-6], P < 0.00001). Increased surgical time was associated with intraoperative TBVL (r = 0.340, P < 0.0001). Discussion: Stemless aTSA is associated with a markedly decreased surgical time and intraoperative TBVL when compared with a SS aTSA. Furthermore, the use of a stemless implant results in a shorter hospital LOS and lower discharge pain scores.